Exploring Nelumbo Nucifera As Traditional Medicine: A Review Of Its Phytochemistry And Ethnopharmacological Activity (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
Nelumbo nucifera Gaertn. (Sacred Lotus), a revered aquatic plant in Asia, it exhibits a broad spectrum of ethnomedicinal and pharmacological properties. Traditionally valued for its cooling, cardiotonic, diuretic, and anti-inflammatory effects, every part of the plant from rhizomes and leaves to seeds and flowers has therapeutic potential. Rich in alkaloids (e.g., nuciferine, neferine), flavonoids, and phenolic acids, it shows diverse pharmacological actions: anti-inflammatory, antioxidant, anticancer, hepatoprotective, hypoglycemic, neuroprotective, and anti-obesity effects. Notably, it demonstrates antiviral (anti-HIV, anti-HSV-1), anti-Alzheimer, antiplatelet, and anti-epileptic activity. Lotus extracts also show promise in reproductive health and skin pigmentation modulation. Recent studies have highlighted its anti-osteoclastogenic potential, isolating 18 compounds from leaves and stems two of which are novel effective in inhibiting osteoclast formation by up to 78%. These findings underscore Nelumbo nucifera’s phytopharmacological significance and support its traditional use while paving the way for further drug discovery and development.